2010
DOI: 10.1016/j.jecp.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Similarity predicts liking in 3-year-old children

Abstract: a b s t r a c tTwo studies examined the influence of similarity on 3-year-old children's initial liking of their peers. Children were presented with pairs of childlike puppets who were either similar or dissimilar to them on a specified dimension and then were asked to choose one of the puppets to play with as a measure of liking. Children selected the puppet whose food preferences or physical appearance matched their own. Unpacking the physical appearance finding revealed that the stable similarity of hair co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 36 publications
6
103
1
Order By: Relevance
“…When children were presented with a similarity condition where the similarity factor was arbitrary (e.g., sticker, mitten) and randomly assigned by an experimenter, 3-year olds and even 11.5-monthold infants did not show preference toward a similar puppet over a dissimilar puppet (Fawcett & Markson, 2010;Mahajan & Wynn, 2012). This result shows that young children do not consider every kind of similarity between them and others as an important factor for initial attraction.…”
Section: Young Children's Attraction Toward Similar Peersmentioning
confidence: 92%
See 3 more Smart Citations
“…When children were presented with a similarity condition where the similarity factor was arbitrary (e.g., sticker, mitten) and randomly assigned by an experimenter, 3-year olds and even 11.5-monthold infants did not show preference toward a similar puppet over a dissimilar puppet (Fawcett & Markson, 2010;Mahajan & Wynn, 2012). This result shows that young children do not consider every kind of similarity between them and others as an important factor for initial attraction.…”
Section: Young Children's Attraction Toward Similar Peersmentioning
confidence: 92%
“…In a study that examined the influence of similarity on initial attraction of 3-year-old children, Fawcett and Markson (2010) showed that 3-year-old children are attracted to peers (puppets) who have similar preference of food and toy as themselves. When children were shown two puppets with different food and toy selection, they chose a puppet that made similar choice as they did.…”
Section: Young Children's Attraction Toward Similar Peersmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently a study found that when the third-party interaction engaged the toddler or created a reciprocal social interaction with the speaker on the video, the toddlers at 24-months-old were able to learn novel words from video (O 'Doherty et al, 2011). Some of the other laboratory studies by exploring preschool children found that children prefer to interact with peers who have similar characteristics as themselves (Fawcett & Markson, 2009). They made interference and respond to the observable third-party conflicts by displaying pro-social behaviors more towards the puppet that was harmed (Vaish et al, 2011).…”
mentioning
confidence: 99%